Estimating HIV incidence among key affected populations in China from serial cross‐sectional surveys in 2010–2014. Issue 1 (16th March 2016) - Cui, Yan; Guo, Wei; Li, Dongmin; Wang, Liyan; Shi, Cynthia X; Brookmeyer, Ron; Detels, Roger; Ge, Lin; Ding, Zhengwei; Wu, Zunyou
Abstract : Introduction: HIV incidence is an important measure for monitoring the development of the epidemic, but it is difficult to ascertain. We combined serial HIV prevalence and mortality data to estimate HIV incidence among key affected populations (KAPs) in China. Methods: Serial cross‐sectional surveys were conducted among KAPs from 2010 to 2014. Trends in HIV prevalence were assessed by the Cochran‐Armitage test, adjusted by risk group. HIV incidence was estimated from a mathematical model that describes the relationship between changes in HIV incidence with HIV prevalence and mortality. Results: The crude HIV prevalence for the survey samples remained stable at 1.1 to 1.2% from 2010 to 2014. Among drug users (DUs), HIV prevalence declined from 4.48 to 3.29% ( p <0.0001), and among men who have sex with men (MSM), HIV prevalence increased from 5.73 to 7.75% ( p <0.0001). Changes in HIV prevalence among female sex workers (FSWs) and male patients of sexually transmitted disease clinics were more modest but remained statistically significant (all p <0.0001). The MSM population had the highest incidence estimates at 0.74% in 2011, 0.59% in 2012, 0.57% in 2013 and 0.53% in 2014. Estimates of the annual incidence for DUs and FSWs were very low and may not be reliable. Conclusions: Serial cross‐sectional prevalence data from representative samples may be another approach to construct approximate estimates of national HIV incidence among key populations. We observed that the MSM population had the highest incidence for HIV among high‐risk groups in China, and we suggest that interventions targeting MSM are urgently needed to curb the growing HIV epidemic.